Impact of Defect‐Rich Carbon Nanofibers Combined with Magnetic Materials on Broadband Electromagnetic Wave Absorption and Radar Cross‐Section Reduction - Ibrahim Abdalla; Ahmed Elhassan; Salma Ali; Malik Yonis Hassan Saty; Ekrema Adam; Lihua Zou; Qingqing Ni; Zhenzhen Xu (Small Structures, 2025)
Carbon nanofibers (CNFs) exhibit inherent dielectric properties that enhance electromagnetic (EM) wave absorption, yet challenges exist in expanding their effective absorption bandwidth (EAB) and improving flexibility. Many studies fail to adequately consider how structural factors influence performance when combining CNFs with magnetic materials. To address these issues, a 1D carbon nanocomposite is developed by embedding magnetic oxide nanoparticles within CNFs using a simple electrospinning technique. This approach improves membrane flexibility by disrupting rigid alignment and introducing dynamic magnetic interactions, while also creating defect‐rich interfaces that increase the amorphous content (61%) of the CNFsF composite, leading to improved EM wave absorption. The unique macro/mesoporous morphology provides internal interfaces and heterogeneous boundaries that effectively trap and dissipate EM waves. As a result, the flexible CNF composites demonstrate significant EM wave absorption performance, achieving a minimum reflection loss (RLmin) of −39.8 dB at 4.64 GHz and an abroad EAB of up to 7 GHz at only 2.5 mm thickness. Computer simulation technology (CST) simulations indicate a maximum radar cross‐section reduction of 21.1 dB m2, highlighting the material's radar stealth capability. This research advances the development of high‐performance materials and offers new strategies for enhancing absorption properties through composite engineering.